2007
DOI: 10.1055/s-2007-993749
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Hypericum and AFLP Markers for Species-Specific Identification of H. perforatum L.

Abstract: One of the top-selling medicinal products worldwide is Hypericum perforatum (St. John's Wort). Despite its cosmopolitan distribution and utilization, little is known regarding the relationship of the bioactive compounds in H. perforatum to the plants from which they are purportedly derived. In this study, amplified fragment length polymorphism (AFLP) analysis of 56 Hypericum accessions, representing 11 species, was conducted to gain a better understanding of diversity within Hypericum species, especially withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
1
30
0
2
Order By: Relevance
“…Additionally, the contribution of 58% of the total amount of molecular genetic diversity observed by among-population difference is indicative of low levels of gene flow between populations. High among-population variation was previously reported in Hypericum species by Percifield et al (2007), Pilepić et al (2008), and Farooq et al (2014). High differentiation among populations is mostly coupled with limited gene flow among them.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, the contribution of 58% of the total amount of molecular genetic diversity observed by among-population difference is indicative of low levels of gene flow between populations. High among-population variation was previously reported in Hypericum species by Percifield et al (2007), Pilepić et al (2008), and Farooq et al (2014). High differentiation among populations is mostly coupled with limited gene flow among them.…”
Section: Discussionmentioning
confidence: 59%
“…Molecular analyses revealed that all the ecotypes were polyclonal, not being dominated by a single genotype, and characterized by different levels of differentiation among multilocus genotypes. Percifield et al (2007) performed AFLP analysis of 56 Hypericum accessions, representing 11 species, to gain a better understanding of diversity within Hypericum species, especially within cultivated accessions of H. perforatum, and to establish a molecular methodology that will provide breeders and regulators with a simple, affordable, and accurate tool with which to identify purported H. perforatum material.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AFLP is a useful method for precise identification of genotype within a short period of time. This method also proves to be very important in plant taxonomy for species-specific identification (Lin et al, 1996, soybean;Waugh et al, 1997, barley;Degani et al, 2001, strawberry;Saunders et al, 1999, 2001, marijuana andopium, respectively;Percifield et al, 2007, Hypericum perforatum L.; Misra et al, 2010, Swertia sp).…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of DNA marker techniques, such as random amplified polymorphic sequence (RAPD) (Juchum et al, 2007;Ro et al, 2007), amplified restriction fragment polymorphism (AFLP) (Percifield, 2007;Yuan et al, 2007) and microsatellite markers (SSR) (Legesse et al, 2007;Tommasini et al, 2003). They are widely applied in species or varieties identification, evaluation of genetic diversity, but few reports are available on systematically comparative analysis of two kinds of testing approaches, such as morphological method and molecular marker method.…”
Section: Introductionmentioning
confidence: 99%